## Search

.## Management Sciences

A. if a < b

B. if a ≤ b

C. if the relationship between a and b cannot be established.

**D. if a > b**

Explanation:

I.(a – 3)(a – 4) = 0

=> a = 3, 4

II. (b – 2)(b – 1) = 0

=> b = 1, 2

=> **a > b**

### Related Mcqs:

- Find the roots of the quadratic equation: x2 + 2x – 15 = 0?

- A. -5, 3 B. 3, 5 C. -3, 5 D. -3, -5...

- Find the roots of the quadratic equation: 2×2 + 3x – 9 = 0?

- A. 3, -3/2 B. 3/2, -3 C. -3/2, -3 D. 3/2, 3...

- The sum of the square of the three consecutive even natural numbers is 1460. Find the numbers?

- A. 18, 20, 22 B. 20, 22, 24 C. 22, 24, 26 D. 24, 26, 28...

- (i). a

^{2}+ 11a + 30 = 0,

(ii). b

^{2}+ 6b + 5 = 0 to solve both the equations to find the values of a and b?

- A. If a < b B. If a ≤ b C. If the relationship between a and b cannot be established D. If a > b...

- I. a

^{2}+ 8a + 16 = 0,

II. b

^{2}– 4b + 3 = 0 to solve both the equations to find the values of a and b?

- A. If a < b B. If a ≤ b C. If the relationship between a and b cannot be established D. If a > b...

## Recent Comments